CONCEPTUAL PRINCIPLES OF MANAGEMENT OF THE DEVELOPMENT OF THE MEDICAL INDUSTRY OF UKRAINE - Багрєєв, Максим В. (Journal of Strategic Economic Research, 2025)
This article is dedicated to the study of the conceptual framework for managing the development of Ukraineʼs medical industry. The strategic role of the medical industry (MI) in ensuring national security, demographic stability and the innovative development of the nation is substantiated. The paper analyzes the key challenges stemming from the full-scale war, European integration processes, and the Fourth Industrial Revolution, which necessitate a reconceptualization of the sectorʼs governance. It is argued that the current model of import dependency and excessive reliance on humanitarian aid is unsustainable, a conclusion supported by WHO data on medicine shortages and the estimated USD 1–26 billion required to rebuild the medical infrastructure. The study examines the current state of development management within the medical industry, using its key component – the pharmaceutical industry (PI) – as a case study. It highlights structural problems, including: economic challenges (an inflationary market growth of 13% in 2024, contrasted with a 20% decline in US dollar volume from USD 5 billion in 2021 to USD 4 billion in 2023); export-import imbalances (a pronounced import dependency, with findings showing that imports constitute 63% of the market in monetary value, while exports are eight times lower); and regulatory barriers (the non-recognition of Ukrainian GMP certificates by the EU). The necessity of transitioning to an innovative management approach for the medical industryʼs development is substantiated. Specifically, a conceptual framework for innovative MI development management is proposed, which is centered on: harmonizing legislation with European regulations (MDR 2017/745, IVDR 2017/746) and establishing a single regulatory authority; fostering an innovation ecosystem that includes public-private partnerships, tax incentives for R&D, production clustering, and export support; digitalizing the industry, from the application of artificial intelligence in preclinical research to the implementation of "smart" manufacturing or Pharma 4.0 (utilizing the Industrial Internet of Things, automation and robotics, and manufacturing execution systems); and overcoming the consequences of the war through enterprise relocation, energy autonomy, and targeted public procurement.